2017
DOI: 10.1017/s0007485317001055
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical responses induced in galls of three Cynipidae species in oak trees

Abstract: Gall-making Cynipidae manipulate the leaves of host plant to form galls where offspring find shelter and food. The relationship between oak gallwasp and biochemical mechanisms of galls still requires a better understanding. So, in this research, protein and phenolic compound contents, as well as the activity of antioxidative enzymes and pathogenesis-related (PR) proteins were determined. Galls caused by asexual generation of Cynips quercusfolii L., Neuroterus numismalis (Fourc.) and N. quercusbaccarum L., as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…However, phenolics in insect galls have also been related to an increase of IAA (indol-3-acetic acid), influencing processes of cell hypertrophy and hyperplasia [ 6 ][ 11 – 13 ]. They are also involved in the antioxidant system, preventing the premature senescence of gall tissues [ 4 5 , 14 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, phenolics in insect galls have also been related to an increase of IAA (indol-3-acetic acid), influencing processes of cell hypertrophy and hyperplasia [ 6 ][ 11 – 13 ]. They are also involved in the antioxidant system, preventing the premature senescence of gall tissues [ 4 5 , 14 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, other studies have also shown that soluble protein levels in galls of the midge Bruggmanniella sp. (Huang et al, 2015) and cynipids (Schönrogge et al, 2000;Allison & Schultz, 2005;Kot et al, 2018) were lower than those in surrounding ungalled tissues.…”
Section: Introductionmentioning
confidence: 75%
“…Other authors have also reported differences in the concentrations of certain secondary compounds as well as certain types of phytohormones in plant gall tissue (Kraus & Spiteller, 1997;Pinkwart, Diettrich, & Luckner, 1998). Kot et al (2017), Li et al (2017) and Hall et al (2017) demonstrated that galls induced by cynipid species and the wasp Leptocybe invasa (Hymenoptera: Eulophidae), respectively, contain high levels of phenolic compounds compared with control tissues. Moreover, increased production of waxes in the gall induced by the insect Baccharopelma spp.…”
Section: Insect-induced Plant Galls and Phytochemistrymentioning
confidence: 95%
“…An interesting aspect of some plant galls is the particular or even radical phytochemistry between these structures and normal plant tissues. Research conducted on galls of different species of plants have revealed that the composition and concentration of chemical substances in these structures can differ from those of other plant tissues and organs Saltzmann et al, 2008;Giron & Huguet, 2011;Huang et al, 2015;Oates et al, 2015;Hall, Carrol, & Kitching, 2017;Kot, Jakubczyk, Karaś, & Złotek, 2017). Tissues near the outside of the gall frequently accumulate high levels of tannins and other chemical compounds related to the process of defense of the gall and, in consequence, of the insect (Ananthakrishnan, 1998;Li et al, 2017;Chen et al, 2018;Nogueira et al, 2018).…”
Section: Insect-induced Plant Galls and Phytochemistrymentioning
confidence: 99%
See 1 more Smart Citation